EVIDENCE OF EUROPEAN ICE SHEET FLUCTUATION DURING THE LAST GLACIAL CYCLE - Boulton G.S.; Dongelmans P.; Punkari M.; Broadgate M. (My University, 2004)
Satellite images provide unique means of identifying large scale flow-generated lineations produced by former ice sheets. They can be interpreted to reconstruct the major elements which make up the integrated, large scale structure of ice sheets: ice divides; ice streams; interstream ridges; ice shelves; calving bays. The evolving form of the European ice sheet during its decay after the Last Glacial Maximum (LGM) is reconstructed by reference to these components and in the context of a new map showing isochrons of retreat. During the retreat phase in particular the time dependent dynamic evolution of the ice sheet and the pattern of ice stream development are reconstructed.Crossing lineations are widespread. The older ones are suggested to have formed during molten bed phases of ice sheet growth and preserved by frozen bed conditions during the glacial maximum, particularly in areas which lay, during deglaciation, beneath ice divides and inter-ice stream ridges. both areas of slow flow and frozen bed conditions.Four phases of growth (A1 to A4) and five phases of decay (R1 to R5) are used to describe the major climatically and dynamically determined stages in the evolution of the ice sheet through the last glacial cycle. The growth and decay patterns are quite different, and associated with major shifts in the ice divide, reflecting growth from the Fennoscandian mountains and decay away from marine influenced margins.